Albania : Income Distribution, Poverty, and Social Safety Nets in the Transition, 1991-1993. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1994)
This paper examines developments in Albania's income distribution and poverty during the transition to a market-oriented economy. It pays particular attention to the impact of price liberalization on the agricultural terms of trade and production, the decline in state enterprise employment, emigrant remittances, and social safety nets. Income and consumption data produce conflicting results. Based on income data, including average presumptive agricultural incomes and state sector wages, there is a significant rise in real income in rural areas and a decline in real income in urban areas. Based on food consumption data, however, a large decline in urban real incomes is implausible. Poverty in both the urban and the rural population was mitigated by the presence of formal social safety nets, as well as informal arrangements in the form of emigrant remittances.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet